(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Today is an age of commerce. Commerce has brought about revolutionary changes in every walk of life. Commerce is a down to earth practical discipline. Commerce is a both knowledge and skill subject. It is an organized system for the exchange of goods between the members of the industrial world. It is the whole system of an economy that constitutes an environment for business.Social changes in the country are also influenced by the development of commerce. Trade and allied activities directly influences every human being. Commerce has become the lifeline of every country. The level of development and the standard of living of the people are linked to the state of commerce in a particular country.